First-line monodrug chemotherapy in low-risk gestational trophoblastic neoplasia: a network meta-analysis - Zhou, Fang; Kemin, Li (Frontiers in Oncology, 2024)
Objective The efficacy of the first-line monodrug chemotherapy has been generally established for low-risk GTN. Most patients can achieve a complete response after the first-line monodrug chemotherapy. However, which monodrug chemotherapy regimen is better for individual patients with GTN is not yet certain. This study aimed to assess the efficacy of first-line monodrug chemotherapy in low-risk gestational trophoblastic neoplasia (GTN). Method Databases, including PubMed, Embase, Web of Science, and Cochrane Library, were searched from inception to November 1, 2022, for case–control studies on first-line monodrug chemotherapy in GTN. Network meta-analysis was performed to compare the efficacy outcome of six monodrug chemotherapy regimens in GTN, with a complete response rate as the endpoint. Result Twenty-four studies were considered eligible, including 9 randomized controlled trials (RCTs) and 15 non-RCTs. A total of 3344 patients with low-risk GTN were involved. Six monodrug chemotherapy regimens were included and analyzed. In descending order of efficacy, these six regimens were VP-16 (5 days), ACT-D (5 days), MTX (5 days), ACT-D (1.25 mg/m2), MTX (8 days), and MTX (30–50 mg/m2) in all study, and five regimens were ACT-D (5 days), MTX (5 days), ACT-D (1.25 mg/m2), MTX (8 days), and MTX (30–50 mg/m2) in RCT. Conclusion Among the six first-line monodrug chemotherapy regimens for low-risk GTN in all study, VP-16 (5 days) was the best in terms of efficacy. And five regimens in RCT, ACT-D was the best. However, the finding needs to be validated through more high-quality clinical studies.